Basic principles of planning animal product national veterinary monitoring - O. I. Ruchnova; O. V. Pruntova; D. A. Lozovoy (Ветеринария сегодня)
The paper presents the results of basic parameter selection and optimization of sample quantity calculation method for chemical (banned and harmful substance residues), microbiological and radiological tests carried out annually within the Plan of National Veterinary Laboratory Monitoring of Banned and Harmful Substances and Residues Thereof in Live Animals, Animal Products and Feeds in the RF by the Federal Centre for Animal Health (FGBI «ARRIAH»).